TRANSMISSION EFFICIENCY OF CASSAVA MOSAIC VIRUS BY THE WHITEFLY (Bemisia tabaci): AN EVALUATION OF INDIGENOUS CASSAVA VARIETIES (Manihot esculenta Cranz) IN KEBBI STATE, NIGERIA - Yusuf, I. J.; Musa, A.; Mohammed, I.U.; Bello, I.; Muhammad, A.; Abubakar, N. G.; Na-Allah, M.S.; Yusif, I. D. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
An experiment was conducted in the Plastic House of Abdullahi Fodio University of Science and Technology, Aliero, to assess the virus transmission efficiency of whiteflies on the major cassava varieties grown in Kebbi State, Nigeria. The treatments consisted of 13 cassava varieties: Bakin Rogo, Dan Ajafa, Jan Rogo, Dan Sangelu, Dan Yola, Sarkin Fawa, Dan Bashalma, Dan Kalaba, Dan Gwamnati, Bahaushe, Mai Jan Kareri, Bakin Icce, and TMS 0505 as the control. The treatments were laid out in a Completely Randomized Design (CRD) replicated three times. Data were collected on the incidence and severity of cassava mosaic disease. The collected data were subjected to Analysis of Variance (ANOVA), and means were separated using the Least Significant Difference (LSD) test at a 5% (P<0.05) probability level. The results revealed a significant difference in disease incidence and severity among all the varieties at the P<0.05 level. The Jan Rogo (100%) and Dan Ajafa (90%) varieties recorded the highest disease incidence, while the lowest incidence was recorded for TMS 0505 (0.0%). The opposite trend was observed for disease severity. The Sarkin Fawa variety (4.00) recorded the highest severity, followed by Bahaushe (3.80), and then TMS 0505 (1.20), which was the control. The research concludes that the Jan Rogo and Sarkin Fawa varieties were the most susceptible among the cassava varieties used by farmers in Kebbi State. It was recommended that farmers use the Dan Gwamnati variety, which showed certain degree of resistance.